KELAYAKAN MEDIA ENSIKLOPEDIA SUB MATERI PEMANFAATAN KEANEKARAGAMAN HAYATI INDONESIA - Nur Fajriani; Syamswisna Syamswisna; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2020)
This study aims to determine the feasibility of the encyclopedia media sub-material utilization of biodiversity in Indonesia in class X high school. The research method used is descriptive qualitative. This research consists of four stages, namely making encyclopedias, validation of encyclopedia instruments, validation of encyclopedias and data analysis. The validation of the encyclopedia media instrument was carried out by two lecturers from FKIP UNTAN's biology education. After the instrument is declared valid then the validation of the encyclopedia media is carried out. The encyclopedia media was validated by two lecturers from Biology Education FKIP UNTAN and three biology teachers who taught the X class determined using perposive sampling techniques namely MAN 1 Sambas, Muhammadiyah Sambas High School and Bina Utama Pontianak High School. Validation assessment uses a Likert scale and data analysis uses the formula Lawshe (1975). Based on the evaluation of 5 validator values of Content Validity Index (CVI) 1.00, this encyclopedia is valid and suitable to be used as a learning medium for the use of Indonesian biodiversity.